KAJIAN KARAKTERISTIK GELOMBANG PECAH DI PANTAI AMAL BARU KOTA TARAKAN - Kahtijah, Siti; Utomo, Edy; Hermansyah, Muhammad (Civil Engineering Scientific Journal, 2022)
ABSTRACT: Amal Baru beach is a coastline that has great potential as a tourist area. Based on direct observation, it has been undertaking a lot of physical changes (damage) in the coastal area. This damage is caused by coastal dynamics processes such as heavy abrasion which has caused a bad impact and raises concerns for a coastal residents. Consequently, it is necessary to have knowledge on the characteristics of the waves occured on the coastline in the development and security of coastal areas and the protection of the sorrounding community. In the study analysis was conducted by using Airy Theory, the data analysis approach employed the airstream data from BMKG Juwata Tarakan. The result of the analysis of wave transformation for 10 years (2010-2019) at Amal Baru Beach obtainend the dominant wind direction from east to west; the fetch length is 224,589 m; breaking wave height ranges from 0.8 m - 2.4 m and breaking wave depth range from 0.38 m - 2.1 m. Ased on the results of analysis, at maximum wind conditions, average winds, and highly occured winds; the speeds of land breeze blowing beetwen 3.5 m/s - 15 m/s, sea wind speeds blowing beetwen 5 m/s - 19 m/s, Wind waves Forecasting Significant height (H) beetwen 0.9 m - 4.8 m, Period (T) beetwen 5.5 s - 10.2 s, Duration (D) beetwen 9 hours - 11 hours. Thus, the result of Analysis for Wave Height (H) is beetwen 0.8 m - 2.8 m, the Depth of Breaking Wave (Hb) is beetwen 0.3 m - 2.1 m, and the angle of incidence of the wave is 8° - 30°. Therefore, it concluded that the wave height generated during the maximum wind speed conditions and hightly occured wind speed is a destructive wave (waves which damage the coastline).Keywords: breaking waves, hindcasting, wave characteristics, Pantai amal baru, refraction, shoaling.ABSTRAK: Kerusakan yang terjadi di Pantai Amal Kota Tarakan diakibatkan oleh proses dinamika pantai seperti abrasi sangat yang berdampak buruk serta menimbulkan kekhawatiran bagi warga pesisir pantai tersebut. Oleh sebab itu dalam pengembangan dan pengamanan daerah pesisir serta perlindungan kepada mansyarakat sekitar maka perlu pengetahuan mengenai karakteristik gelombang yang terjadi di pantai tersebut. Dalam penelitian ini analisa dilakukan menggunakan Teori Airy, pendekatan data analisa menggunakan data angin dari BKMG Juwata Tarakan. Hasil analisa transformasi gelombang selama 10 tahun (2010-2019) di Pantai Amal Baru diperoleh arah angin yang mendominasi dari timur menuju kearah barat, panjang fetch 224,589 m, tinggi gelombang pecah berkisar antara 0,8 m â€“ 2,4 m dan kedalaman gelombang pecah berkisar antara 0,38 m - 2,1 m. Dari hasil analisa, pada kondisi angin maksimal, angin rata-rata, dan angin yang sering terjadiÂ  Kecepatan Angin Darat yang bertiup antara 3,5-15 m/s, Kecepatan Angin Laut yang bertiup antara 5 - 19 m/s, Peramalan Gelombang Angin Tinggi signifikan (H) antaraÂ  0,9 - 4,8 m, Priode (T) antara 5,5 - 10,2 s, Durasi (D) antara 9 - 11 jam, sehingga hasil Analisa untuk Tinggi Gelombang (H) antara 0,8 - 2,4 m, Kedalaman Gelombang Pecah (Hb) antara 0,3 - 2,1 m, dan Sudut datang gelombang 8Ëš- 30Ëš. Sehingga dapat disimpulkan bahwa tinggi gelombang yang dihasilkan pada saat kondisi kecepatan angin maksimal dan kecepatan angin sering terjadiÂ  merupakan gelombang destruktif (gelomban yan dapat merusak pantai).Kata kunci: Gelombang pecah, hindcasting, karakteristik gelombang, Pantai amal baru, refraksi, shoaling.